Disaster nursing skills, knowledge and attitudes required in earthquake relief: Implications for nursing education. (18th February 2015) - Yan, Y.E.; Turale, S.; Stone, T.; Petrini, M.
<x xml:space="preserve">Abstract</x> Background Globally, nurses becoming more aware of getting better prepared for disaster relief, but in China, disaster nursing knowledge, courses and research are still limited. Introduction China has long been prone to disasters, but disaster nursing education and training is in its infancy. Aim This study explored the skills, knowledge and attitudes required by registered nurses from across China who worked in the aftermath of three large earthquakes to try to determine future disaster nursing education requirements. Method The Questionnaire of Nurses' Disaster Nursing Skills at Earthquake Sites, assessing nursing skills, knowledge and attitudes, was distributed to 139 registered nurses in 38 hospitals in 13 provinces across China who had worked in one or more earthquake disaster zones. Descriptive statistics were used for quantitative data, and content analysis for qualitative data. Results Eighty‐nine questionnaires were returned, a response rate of 68.3%. No respondent had ever received specific disaster nursing training prior to their post‐earthquake nursing. Skills most often used by respondents were haemostasis bandaging, fixation, manual handling, observation and monitoring, debridement and dressing, and mass casualty transportation. Respondents identified that the most important groups of skills required were cardiopulmonary resuscitation; haemostasis, bandaging, fixation, and manual handling; and emergency management. They emphasized the need for psychological care of victims as well as that of fellow health workers. Conclusion No respondent had ever received disaster nursing training prior to engagement at the earthquake disaster sites. All believed that there were important gaps in their knowledge and skills, and supported disaster nursing courses in the future. Implications for nursing and health policy China urgently needs to develop disaster nursing courses, with the support of nurse leaders, educationalists and government, to implement training using an all hazards approach in accordance with international best practice and trainees' background clinical experience and knowledge.